Influence of reconstruction parameters on the quality of the diagnostic image - Yaheni V., Emelyanenko; Igor G., Tarutin (Journal of the Belarusian State University. Ecology, 2020)
Positron emission tomography combined with computed tomography is an innovative and rapidly developing method of radionuclide diagnostics. Tomographs are equipped with a powerful hardware-software complex. For the effective use of equipment, a full-fledged study of the capabilities of the software and the operating modes of the device is necessary. Software features allow the user to influence the quality of the diagnostic image. Using time-of-flight technology, additional correction algorithms can also affect the contribution of the noise component and contrast. These aspects confirm the need for research aimed at harmonizing and optimizing research methods. In this paper, we estimated the impact of the duration of the study on image quality, taking into account the technical capabilities of the equipment. The influence of the number of iterations and subsets of the reconstruction algorithm, as well as the scattering function on the image quality are considered.